Ocular side effects of systemic isotretinoin - a systematic review and summary of case reports - Olivia Lamberg; Arianna Strome; Foster Jones; Julia Mleczek; Adrienne Jarocki; Jonathon P. Troost; Yolanda Helfrich (Taylor & Francis Group, 2023)
Background: Isotretinoin is frequently used for treatment of severe nodulocystic and papulopustular acne, however use is limited by mucocutaneous, ocular, and systemic side effects. Objective: (1) provide a systematic meta-analysis of ocular side effects during isotretinoin use and their corresponding incidences; (2) provide a narrative summary of ocular side effects during isotretinoin use reported in case reports. Methods: A systematic database search using predefined search terms was performed in PubMed, EMBASE, and Scopus from inception to 5 March, 2021. Predetermined inclusion and exclusion criteria were used to select included studies. In total, 53 original studies qualified for meta-analysis, and 41 case reports/series qualified for narrative results. Results: The studies included in the meta-analysis reported incidences of various ocular side effects including dry eye, eye sensitivity, vision changes, and ocular inflammatory conditions. Incidences across studies did vary, leading to considerable heterogeneity. The narrative results summarize more uncommon, but equally important, ocular side effects. Conclusions: Dry eye is the most commonly reported ocular side effect. Other less common, but more serious, ocular side effects including vision changes can occur. We recommend that isotretinoin prescribers monitor for dry eye. Limitations include the heterogeneity of reported incidences of ocular side effects between studies.